THE PURIFICATION RECOMBINANT TSA PROTEIN AND CONFIRMATION WITH SDS-PAGE AND WESTERN BLOT - NARGES KHABAZZADEH TEHRANI,; FATEMEH TABATABAIE, (International Journal of Pharma and Bio Sciences, 2015)
The TSA protein may be helpful as an ingredient of a subunit vaccine against leishmaniasis. When tested under similar experimental conditions, it was able to induce similar partial protective effects. The aim of this study was the production, purification new construction of TSA protein. In this regard, the recombinant plasmid pET28-a+used for TSA expression constructed with the TSA gene of cutaneous leishmaniasis fused with his-tag. This recombinant clone over expressed in Escherichia coli BL-21 (DE-3).The expressed fusion protein found almost completely in the insoluble form in cell lysate. The purification was performed under denaturing conditions in the presence of 8M urea by Ni–NTA column and dialysis. The purified recombinant proteins confirmed western blot analysis utilized polyclonal antiserum. Therefore, such an association of antigens increased the number of targeted epitopes by immune system with the prospects the responses are at least additive if not synergistic.